PENGARUH INFRASTRUKTUR DASAR DAN SOSIAL TERHADAP PERTUMBUHAN EKONOMI DESA TERTINGGAL - DEWI W, NILA; Gusni, Gusni (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.02.TAHUN 2019, 2019)
One of the structural and developing economic problems today is about disparity. This is done by the ratio of the province in 2016, which is equal to 0.402 which has exceeded the ratio of Indonesia's gini. There are still many areas or regions in Indonesia that are included in the region / city which is also a phenomenon that indicates inequality. The challenge to provide adequate infrastructure, especially basic and social infrastructure, is the focus of attention in encouraging economic growth. Therefore, in this study the author will try to analyze various things from sanitation, clean water, electricity, education, health, and economic development in Garut Regency. Through the processing of data obtained from village potential data collection (Podes), an analysis that produces regression analysis in the 2008, 2011 and 2014 periods can be used as an indicator of village economic success. The results of the study show that only social infrastructure instruments significantly influence the output of the village so that the right strategy is needed as a recommendation for local governments in order to create inclusive economic development.